2019
DOI: 10.1103/physrevb.100.214510
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic damping and wave vector dependent susceptibility of the spin fluctuations in La2xSrxCuO4 studied by resonant inelastic x-ray scattering

Abstract: We report high-resolution resonant inelastic x-ray scattering (RIXS) measurements of the collective spin fluctuations in three compositions of the superconducting cuprate system La2−xSrxCuO4. We have mapped out the excitations throughout much of the 2-D (h, k) Brillouin zone. The spin fluctuations in La2−xSrxCuO4 are found to be fairly well-described by a damped harmonic oscillator model, thus our data allows us to determine the full wavevector dependence of the damping parameter. This parameter increases with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 53 publications
8
21
0
Order By: Relevance
“…1 (a-c) and compared to the INS results taken from literature when available [2,21]. The LCO dispersion is almost superimposed to the INS data over the whole Brillouin zone in agreement with previous literature [3,24,36]. In SCOC, the agreement is very good everywhere except close to the X-point.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…1 (a-c) and compared to the INS results taken from literature when available [2,21]. The LCO dispersion is almost superimposed to the INS data over the whole Brillouin zone in agreement with previous literature [3,24,36]. In SCOC, the agreement is very good everywhere except close to the X-point.…”
supporting
confidence: 86%
“…These differences in the cross sections stimulated a close comparison of the two techniques, and some doubts were raised on the possibility of deriving the actual spin dynamical structure factor S(q, ω) from RIXS data. Indeed, in the very first RIXS work Braicovich et al [35] had already shown that in La 2 CuO 4 the single magnon energy dispersion in INS and RIXS coincide almost perfectly, a fact that has been recently confirmed more extensively [36]. However, Plumb et al [21] pointed out some discrepancies in the magnetic excitation spectrum (d-f): RIXS spectra at (0.4,0) measured with π incident photon polarization (black circles) and their main constituents obtained by a phenomenological fitting (red line): Gaussian elastic peak (brown), two resolution limited phonon contributions (pink), single magnon with Fano lineshape (blue), even order multimagnons (green).…”
mentioning
confidence: 78%
“…Explicitly, we show that intense and propagating paramagnons persist in the metallic phase along the anti-nodal (Γ-X) Brillouinzone (BZ) direction in wide doping range, but become rapidly overdamped along the nodal (Γ-M ) line. This reflects the experimental trends for multiple copperoxide families [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Also, plasmons are shown to exhibit a substantial three-dimensional character.…”
supporting
confidence: 65%
“…Itinerant carriers are expected to cause Landau overdamping of spin-wave modes, particularly after AF order has been suppressed. On the contrary, resonant inelastic x-ray scattering (RIXS) and inelastic neutron scattering experiments demonstrate that robust paramagnons persist across whole hole-doping phase diagram [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In addition, RIXS provides evidence for lowenergy charge modes (acoustic plasmons) in both holeand electron-doped cuprates [20][21][22][23][24][25].…”
mentioning
confidence: 99%
“…The number of hole carrier changes spin excitation in cuprates. Recent measurements of spin excitation in La 2−x Sr x CuO 4 by resonant inelastic x-ray scattering (RIXS) for tuned for the Cu L edge have shown that energy difference between peak positions near q = (π, 0) and q = (π/2, π/2) increases with increasing hole carriers [15,16]. In fact, the peak energy at q = (π/2, π/2) is almost a half of that at q = (π, 0) in the overdoped region [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%